Mediation Based on the Value of Pacta Sunt Servanda as a Regulation of the Interests of Creditors and Bank Debtors in Cessie - Suhardana, Nyoman; Suhariningsih, Suhariningsih; Winarno, Bambang; Permadi, Iwan (CV. AFDIFAL MAJU BERKAH, 2024)
Receivables are the right to collect debts, a means of fulfilling civil obligations, a continuation of the credit agreement contract that must be held. The principle of Pacta Sunt Servanda as the foundation of giving direction, purpose, and fundamental value and ethical judgement to debts with property collateral with a time limit determined by the parties. However, the need for money when the receivables are not yet due encourages the receivables to be transferred into cessie, doctrinally the holder of the eigendom right has the power to eigenaar freely and to act freely on the property with full sovereignty, even so, the problem arises with the submission following the formal rules of cessie raises legal consequences, if without being notified, or in writing has been acknowledged and approved. This article questions whether the submission of receivables in the form of a unilateral legal action through cessie reflects the value of pacta sunt servanda which provides equality and justice for the parties? By applying a normative juridical research method based on a statutory approach, a legal conceptual approach, and a case approach, it strengthens the results prescriptively analytically, related to cessie which is worth justice being a hope for the business world, preventing potential legal uncertainty, avoiding potential disputes over the implementation of the transfer of receivables, preventing economic losses, by internalising the value of legal certainty and justice. The value of pacta sunt servanda in this case relates to the equal position between the creditor and the debtor, this aspect also emphasises the guarantee of human rights for the parties to the agreement, as well as legal certainty and predictability in the process of fulfilling the provisions of the rights and obligations of the agreement agreed by the parties